Jejunal atresia due to heterotopic pancreatic intussusception - So-Hyun Nam; Song-Hee Han (Elsevier, 2021)
Jejunal atresia is a common cause of neonatal intestinal obstruction that requires surgical correction and may be caused by intestinal volvulus, intussusception, or internal hernia. A 1-day-old female infant was referred to our hospital for evaluation of bilious vomiting. Under the impression of jejunal atresia, laparotomy was performed on the 3rd day after birth. A type I jejunal atresia was detected following jejunal intussusception caused by a 2.5-cm intraluminal mass. Small bowel resection and anastomosis were performed, and the infant recovered uneventfully. The mass was histologically confirmed as heterotopic pancreas. Here, we describe our successful experience with jejunal atresia caused by heterotopic pancreatic intussusception.